Perkembangan Motorik Anak Usia Dini - Adin Suryadin; Endah Tri Wahyuningsih (STAI Terpadu Yogyakarta, 2023)
Motoric development in early childhood is one aspect of development that is very important in child development, by looking at the overall motor development of children at an early age we can see how other aspects develop. There are two motor skills in children, namely gross motor and fine motor, each of which has its own indicator of ability. This study aims to look at the development of children's motor skills at the age of 4-5 years, because at the age of 4-5 years the child's motor skills are clearly visible, both fine motoric and gross motoric. This study uses a data collection method with observation checklists, which is an informal observation method where the observer has determined the behavioral indicators to be observed from the subject in one table. The research location was for students of TKIT Yaummi Fatimah Pati class A (age 4-5 years), totaling 23 students. the results of the research on children's motor skills in class A TKIT Yaumi Fatimah Pati in general are in the good category with an average percentage of gross motor skills of 83% and fine motor skills of 84%, with the highest score being able to score 100% there are 4 children, the lowest is 2 with an ability score in the percentage of 56%, while the average average score between 70-80% is 6 children.